2012
DOI: 10.1371/journal.pone.0052583
|View full text |Cite
|
Sign up to set email alerts
|

PTH1 Receptor Is Involved in Mediating Cellular Response to Long-Chain Polyunsaturated Fatty Acids

Abstract: The molecular pathways by which long chain polyunsaturated fatty acids (LCPUFA) influence skeletal health remain elusive. Both LCPUFA and parathyroid hormone type 1 receptor (PTH1R) are known to be involved in bone metabolism while any direct link between the two is yet to be established. Here we report that LCPUFA are capable of direct, PTH1R dependent activation of extracellular ligand-regulated kinases (ERK). From a wide range of fatty acids studied, varying in chain length, saturation, and position of doub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 69 publications
(87 reference statements)
1
12
1
Order By: Relevance
“…Note, EPA appears more potent in the FRET assay than in the ERK assay due to differences in treatment concentrations. Overall, our results are similar to those we earlier observed for the PTH1 receptor [1] and consistent with other studies in which specific GPCRs have been shown to become activated by fatty acids in a length-dependent manner [48][51].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Note, EPA appears more potent in the FRET assay than in the ERK assay due to differences in treatment concentrations. Overall, our results are similar to those we earlier observed for the PTH1 receptor [1] and consistent with other studies in which specific GPCRs have been shown to become activated by fatty acids in a length-dependent manner [48][51].…”
Section: Discussionsupporting
confidence: 93%
“…The lipid bilayer effectively increases the concentration of LCPUFA in GPCR environment thereby increasing the probability of their interaction. In contrast to our earlier report on PTH1 receptor [1] we did not observe synergism from simultaneous stimulation by BK and LCPUFA (Fig. 2 A, 5 B, 5 C) supporting the hypothesis that EPA acts through the orthosteric site of B 2 R. However due to the high concentrations of LCPUFA in the membrane, contributions from allosteric and nonspecific interactions cannot be excluded.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Of interest, interventions that reduced oxidative stress partially restored renal klotho expression in animal models [28]. As an alternative explanation, n-3 fatty acids could act directly on the PTH receptor, a potent inducer of FGF23 [29]; yet adjustment for phosphate, calcium and PTH did not change the observed association between n-3 fatty acid or fish intake and FGF23. Serum FGF23 levels have been shown to be influenced by phosphate-rich foods, particularly by protein from animal sources.…”
Section: Discussionmentioning
confidence: 99%